1979
DOI: 10.1113/jphysiol.1979.sp012771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nerve impulses on threshold of frog sciatic nerve fibres.

Abstract: SUMMARY1. The firing thresholds of single myelinated fibres of frog sciatic nerves were monitored as a function of impulse activity in the fibre. The threshold was given by the number of coulombs in current pulses that excited a particular fibre half the time when delivered to the whole nerve. Threshold was tracked by a device that incrementally decreased the number of coulombs in the current pulse whenever the fibre responded and increased the pulse if it did not respond.2. There was a pattern to the after-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 36 publications
3
80
0
Order By: Relevance
“…With repetitive stimuli, intact sensory axons show a progressive increase in action potential conduction latency (Raymond 1979;George et al 1984;Carley and Raymond, 1987;Shin et al 1997). To test whether regenerated axons also exhibit increased conduction latency, we compared the latency of the 1 st and the 5 th response in a train of stimuli.…”
Section: Conduction In Regenerated Axons Is More Sensitive To Increasmentioning
confidence: 99%
“…With repetitive stimuli, intact sensory axons show a progressive increase in action potential conduction latency (Raymond 1979;George et al 1984;Carley and Raymond, 1987;Shin et al 1997). To test whether regenerated axons also exhibit increased conduction latency, we compared the latency of the 1 st and the 5 th response in a train of stimuli.…”
Section: Conduction In Regenerated Axons Is More Sensitive To Increasmentioning
confidence: 99%
“…When the input voltage is beyond the threshold voltage of the resting potential, a contraction of muscle would be induced by opening the valve of the action potential. 17 For a frog's sciatic nerve, the cells' resting potential ranges from −60 to −80 mV, and a voltage input of at least 50 mV at 1 Hz is necessary for innervation of the sciatic nerve.…”
mentioning
confidence: 99%
“…One set, used for conditioning stimuli, was located upstream from the set of test electrodes used to measure the threshold. The use of a separate pair of electrodes for conditioning ensured that any changes in the current distribution at the electrode caused by passing the conditioning stimuli did not disturb the threshold measurement (Raymond, 1979;Carley, 1984). The stimulating cathode was normally at least 2 cm from the cut end of the nerve, when the stimulating electrode was closer than 1 cm to the cut end, the after-effects of activity were attenuated, and in some cases the depression phase was even inverted.…”
Section: Methodsmentioning
confidence: 99%
“…A given node generates currents which conduct through passive internodal regions to trigger action potentials at the next node (Huxley & Stiimpfli, 1949;Tasaki, 1953). Measurements of firing threshold in single axons from human median nerve (Bergmans, 1968a, c) and frog sciatic nerve (Raymond, 1979) have revealed that impulse activity in a fibre is followed by a characteristic sequence of oscillatory transients in the firing threshold. In frog axons each conducted impulse is followed by a brief (< 7 ms) refractory period during which the firing threshold is elevated.…”
Section: Introductionmentioning
confidence: 99%